Predictive techniques in medical imaging: opportunities, limitations, and ethical-economic challenges - Luca Saba; Ernesto d’Aloja (npj Digital Medicine)
Predictive techniques in medical imaging offer transformative opportunities for early diagnosis and personalized care but raise complex ethical, legal, and economic challenges. This paper explores current advancements, regulatory implications, and risks such as overdiagnosis, alert fatigue, and information overload, emphasizing the urgent need for multidisciplinary frameworks to ensure responsible implementation and sustainable integration into healthcare systems.